A rare Case Report of Hurler syndrome with multisystem involvement including glucose intolerance - Thapa, S; Upadhyay, TL; Paudel, B; Gyawali, R (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Mucopolysaccharidosis type I (Hurler syndrome) is a rare autosomal recessive inborn deficiency in the metabolism of glycosaminoglycans (GAGs) heparan sulfate and dermatan sulfate, resulting from deficiency of Alpha-L-iduronidase enzyme. An interesting case of a 19 year old male with a combination of skeletal, neurological, ophthalmologic, and radiological findings with MPS I-(Hurler syndrome) has been presented here in this case report.